The Influence of Corporate Governance Perception Index and Profitability on Company Performance in Companies Registered with the Indonesian Institute for Corporate Governance 2017 – 2022 - Diza Muzdhalifa; Siti Jamilah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the effect of the Corporate Governance Perception Index (CGPI) and profitability on company performance in companies listed on the Jakarta Islamic Index (JII) from 2018-2023. CGPI is used as an indicator to evaluate the quality of corporate governance, while profitability is measured using Market Value Added (MVA) as a proxy. This study focuses on companies that meet certain Sharia principles and financial criteria and are selected based on a purposive sampling method. The results of this study are expected to provide theoretical contributions to the development of the concept of corporate governance in the context of Sharia, as well as provide empirical evidence regarding the relationship between CGPI, profitability, and company performance. In addition, this study aims to provide insight for companies and the public to understand the impact of CGPI implementation on company value while enriching the literature on Sharia economics. This study uses a quantitative approach with secondary data from financial reports and CGPI ratings.